Development of creative character training program among student of UNJ: Karakter Kreatif - Wulan, Dwi Kencana (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2019)
Creative ideas are not only generated from creative thinking, but also need to be supported by individual creative character (nonaptitude creativity). This study aims to obtain data about problems in developing creative characters in students. The results showed aspects of creative characters that still need to be developed are high curiosity, like challenges and dare to take risks. Based onthis we design a training program to develope creative character. This training programfocuses on providing learning through direct experienced, in order to develop aspects high curiosity, like challenges and dare to take risks of students